Between Place: Food Consumption and Spaces of Inclusion and Exclusion in Montpellier, France - Munetz, Jonathan (My University, 2011)
?If you are lucky enough to have lived in Paris as a young man, then wherever you go for the rest of your life, it stays with you, for Paris is a moveable feast,? wrote Ernest Hemingway about his time there in the 1920s.1 He surely had more in mind than profiteroles, foie gras, and terrines when he penned these words. Hemingway?s Paris was electric, pulsing with the caf? culture of the Left Bank at the pinnacle of the modern age. This was Paris?a Bohemian, exuberant ideal of how it must be to live as an expatriate, especially an American, in France. What Hemingway attempted to capture with words, George Gershwin set to music. The melodies of An American in Paris, composed in 1928, evoke a traveller?s path through the city at that time.2 If you have a musical imagination, perhaps you can feel the place in that era through Gershwin?s tone poem; or if you are a more literary sort, maybe you can picture Hemingway?s city?in the company of Gertrude Stein, F. Scott Fitzgerald, and Pablo Picasso. Such a place now exists only as sets of recollections. Yet this Paris of the past lives on. What is more, this long-past or maybe merely mythic capital and all of its romantic evocations are projected onto the entire country, if only in our minds. This is what it must be like to live as a foreigner in France.
Includes bibliography
Keywords: Food Consumption; Montpellier, France